Recovery after exercise in the heat--factors influencing fluid intake - Mack, G. W. (International Journal of Sports Medicine, 1998)
The restoration of body fluid balance following dehydration induced by exercise will occur through regulatory responses which stimulate ingestion of water and sodium ions. A number of different afferent signalling systems are necessary to generate appropriate thirst or sodium appetite. The primary sensory information of naturally occurring thirst is derived from receptors sensing cell volume and the volume of the extracellular fluid compartment. Sensory information from the oropharyngeal region is also an important determinant of thirst. The interaction of these various afferent signalling systems within the central nervous system determines the extent of fluid replacement following dehydration.